3D screen printing for the fabrication of small intricate Ti-6Al-4V parts. (December 2015) - Jurisch, M.; Studnitzky, T.; Andersen, O.; Kieback, B.
Abstract : For the production of complex shaped titanium parts huge advances have been made by powder metallurgy (P/M) during the last years. However, when it comes to miniaturized parts with intricate inner structures like closed channels without entrapped powder and high aspect ratios conventional P/M methods are stretched to their limits. To remedy this shortcoming, Fraunhofer IFAM Dresden uses 3D screen printing, a modified screen printing process based on a powder-binder mixture which is printed layer-by-layer to the desired shape followed by debinding and a conventional sintering step. Especially for small parts a productivity of several million parts per year is achievable. The objective of this work is to demonstrate the possibility to manufacture complex designs based on titanium including thin walls down to 120 μm. Therefore, pre-alloyed gas atomized Ti-6Al-4V powder was used. Analysis of part accuracy, resulting porosity, impurity level and mechanical properties were performed.